Placenta location, a prognostic determinant for the incidence of preeclampsia - Fariba Alikhani; Marzieh Aalinezhad; Mahshid Bahrami; Mahsa Geravandi (BMC Pregnancy and Childbirth)
Abstract Background Preeclampsia is one of the complications of pregnancy with uncertain etiology. Nevertheless, it is believed that the condition may arise due to abnormal trophoblastic invasion, resulting in vascular remodeling and increased resistance in the spiral arteries. It is assumed that the location of the placenta might have contributed to the formation of trophoblastic invasion and further placental supply. The current study aims to investigate the association of placental location with the incidence of preeclampsia. Methods The current case-control study was conducted on 206 primigravid pregnant woman undergone routine screening ultrasonography study between 14 and 26 gestational weeks to determine the location of the placenta (anterior, posterior, or lateral). The pregnant women were categorized as cases that met the criteria of high-risk for preeclampsia (n = 106) or the controls (n = 100). Results Logistic regression analysis identified increased age (OR: 1.047, 95% CI: 1.02–1.07, PPP-value = 0.033), BMI > 25 kg/m² (OR: 4.61, 95% CI: 1.02–10.02, PPP-value = 0.038), and anterior placental location (OR: 2.79, 95% CI: 1.08–9.43, PPP-value = 0.038) as significant predictors of preeclampsia. Posterior placental location was initially associated with preeclampsia (PPP-value = 0.049), but this association was not robust and may reflect random variation. Conclusion This study identified anterior placental location, increased maternal age, and BMI above 25 kg/m² as significant predictors of preeclampsia. These findings suggest that healthcare providers should closely monitor pregnant women with anteriorly located placentas, advanced age, or elevated BMI. Regular blood pressure monitoring and urine protein screening for individuals with anterior placental location could facilitate early diagnosis and management of preeclampsia. While posterior placental location showed a potential association, it was less consistent, and further research is needed to confirm its role.